Normatywne zasady brakowania i niszczenia materiałów Służby Bezpieczeństwa w Ministerstwie Spraw Wewnętrznych (1956–1990) - Koller, Stanisław (Pamięć i Sprawiedliwość, 2012)
Documents drafted by the SB of the Polish People’s Republic (Polska Rzecz-pospolita Ludowa) were submitted to the archive of Office “C”. They were subject to the provisions on the handling of archive files at the Ministry of Interior. Appropriate regulations, instructions and lists of files were issued by the minister in cooperation with the director of Office “C”. They also contained the principles of disposal and destruction of archived documents. In the years 1956–1990, the following regulations concerning this area were issued: no. 00123/57, 0127/57, 0107/68, 08/71, 034/74, 030/79, 049/85. Current top secret operational documentation or secret operational documentation of special significance was destroyed under the regulations, instructions and the list of issues that constituted state secrecy, issued by the minister. In the years 1956–1990, the following regulations concerned that issue: no. 70/60, 0101/60, together with Appendix no. 2, 0078/66, 89/72, Instruction to Regulation no. 08/75, 60/83, 26/87. In the case of some departments (e.g. Office “W”), separate provisions were issued owing to the special nature of the documentation drafted at those units. The main factor determining the period of file archiving was the operational, practical, scientific and historical value of the collected documents. Under the provisions of law, it was necessary to destroy the documents in the presence of a committee. Furthermore, a protocol had to be drafted on the disposal or destruction of the documents. The performance of the procedure had to be kept secret, and the disposal protocol had to be stored at the archive. In the years 1957–1985, during the process of revising the regulations, the file archiving period was notably shortened, which was the result of political changes. In 1989 – in compliance with the Announcement of Minister of Interior Czesław Kiszczak of 17 February 1989 on the list of legal acts that are valid at the Ministry of Interior – the issue of material destruction at the Ministry of Interior was governed by regulations no. 60/83, 02/85, 049/85 Nr 26/87. Apart from those documents, the directors of some departments issued their own regulations on the disposal of the documents drafted at their units. The disposal and destruction of documents at Office “C” was governed by the logic of a Soviet state that was not subordinate to any control. The liquidation of the SB archives was aimed at removing evidence of the criminal activities of the officers of the state apparatus and protecting them from penal liability. The destruction of SB materials enabled securing the interests of special services of the Union of Soviet Socialist Republics that cooperated with SB. The employees that issued these normative acts were aware of this.